Drinking-Water and Human Health Challenges in the 21st Century - Makris, Konstantinos C. (My University, 2020)
Water and human health issues are intertwined within a changing urban setting. There is a momentum of societal demand to act on the aging drinking water pipe infrastructure to protect human health and at the same time to devise control options that will promote further the well-being and quality of urban life in the developed world. The main objective of this work was to critically review the main challenges, opportunities, and risks associated with drinking water's current and emerging pressures as exerted on human health in urban centers of middle- and high-income countries. Discussion about drinking-water distribution systems did not focus on their portion extending from the water meter to the home tap, i.e. the premise plumbing system characteristics. One city does not hold a single water quality metric that remains constant because it changes in the urban space and time. Bigger urban centers will be differentially more complex to address water and health risks because of their numerous neighborhoods (district-metered areas, DMA) being spread apart geographically in large distances. The water and health issues are multidisciplinary in nature and demand the close cooperation among health scientists, engineers, environmental scientists, social scientists, economists, and policymakers to address each city's unique risks.
Keywords: environmental health; pollution; biofilms; scales; drinking water; exposure